Licensing as a commercialization strategy to improve varietal adoption in Ghana - Kuhlmann, Katrin; Nalinya, Adron Naggayi; Botey, Mireku; Gichuru, Lilian; Puozaa, Doris Kanvenaa; Onsando, James; Ahenda, Joseph; Mujaju, Claid; Ojiewo, Chris Ochieng (CIMMYT, 2025)
Ghana’s Council for Scientific and Industrial Research (CSIR), through its Crops Research Institute (CRI) and Savanna Agricultural Research Institute (SARI), is responsible for developing improved crop varieties and has developed hundreds of varieties over the years. However, these public research institutes face significant funding challenges that constraint breeding activities, variety testing and release, maintenance and provision of early generation seed (EGS), and handover to seed systems actors. This policy brief summarizes findings from a consultative meetings and workshops held in 2024 to understand how CSIR-CRI and CSIR-SARI can explore licensing to enhance varietal adoption and commercialization. It was identified that the licensing model currently implemented by the CSIR could have broader implications for public breeding objectives or farmers' access to improved varieties. Low awareness of Plant Breeders’ Rights (PBR) and intellectual property rights (IPR) regulations among staff, gaps in managing licensing agreements, and weak private sector engagement undermine crop variety commercialization through licensing. Recommendations based on stakeholder consultations included the development of an improved licensing strategy and standardadized guidelines, awareness creation, capacity building in variety licencing models, institutionalization of EGS supply processes, and improved engagement with the private sector.